GIS BASED DECISION SUPPORT SYSTEM FOR SEISMIC RISK IN BUCHAREST. CASE STUDY – THE HISTORICAL CENTRE - DIANA GHEORGHE; IULIANA ARMAS (Journal of Engineering Studies and Research)
Because of the increasing volume of information, problem decisions tend to be more difficult to deal with. Achieving an objective and making a suitable decision may become a real challenge. In order to better deal with decision making, decision support systems (DSS) have been developed. The decision support systems (DSS) can be used in any kind of a decision-making process and are very suitable in situations that involve a lot of stakeholders and a large number of criteria. DSS offers support in the decision-making process (how a decision should be made), and it does not focus on the result (what decision that should be made). DSS can also involve a large number of stakeholders and criteria, in the same time. A limitation of this method is that, regardless of the mathematical results, the final decision has to be made by the decision maker. Depending on the nature of the decision problem, a decision maker can use decision support systems (DSS), if the decision problem is economic or technical, and spatial decision support systems (SDSS), if the decision maker is faced with a spatial decision problem. The main objective of the present study is to apply a spatial decision support system in order to find a suitable shelter in the historical centre of Bucharest City in the post-disaster phase, in case of an earthquake occurrence. The present work represents a first step in applying SDSS in the context of the seismic risk in Bucharest. For the present paper, the SMCE Module for ILWIS 3.4 was used. The method included the following steps: structuring the problem in a decision tree, applying standardization and weighting methods to the criteria, finding suitable alternatives and choosing one of the alternatives. The results show that several buildings can be used as a shelter and among these are ‘Creditul Roman’ Bank Palace, the National History Museum and the National Bank of Romania.